Fractal analysis to determine JRC on sandstones and its correlation to SRF, Ende-Lianunu Regency, East Nusa Tenggara Province, Indonesia - Tien Veny Vera; Sari Bahagiarti Kusumayudha; Singgih Saptono; Kurniawan Kurniawan (International Journal of Advances in Applied Sciences, 2023)
The study area is located in Ende-Lianunu Regency, East Nusa Tenggara Province, Indonesia, with mountainous and hilly morphology, and is part of the Kiro Formation which is composed of tuffaceous sandstones. Discontinuities in the sandstone are in the form of bedding planes and joints, which affect the mechanical properties of the rock mass, reduce its strength, and affect slope stability. The discontinuity condition that affects mechanical behavior is surface roughness. This research aims to define the fractal dimension value of surface roughness using a box-counting method, joint roughness coefficient (JRC), and simulate the strength reduction factor (SRF) value on slopes that have a certain JRC. The fractal dimension of fine-grained samples = 1.0010 and coarse-grained = 1.0056. The average JRC value is 6.25 (Range 4-6). Simulation at JRC 0-20, gives different SRF values. On slopes with JRC = 0, the critical SRF = 1.35. If JRC = 20, the critical SRF = 1.47. It can be inferred, that the fractal dimension of the roughness of the sliding plane correlates with JRC and SRF. As the fractal dimension value increases, so do the JRC and SRF values, resulting in more stable slope conditions.